2014
DOI: 10.4018/978-1-4666-5880-6.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Data Centre Operations in the UK

Abstract: The purpose of this chapter is to provide an exploratory review of the sustainability agendas being addressed and publicly reported by the UK's leading data centre operators. The chapter begins with a brief discussion of the characteristics of sustainability and an outline of the origins and development of data centres within the UK. The chapter draws its empirical material from the most recent information on sustainability posted on the UK's leading data centre operators' corporate web sites. The findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Despite being considered as a nascent asset investment class, the increasing significance of the alternative property sectors has attracted a number of empirical investigations on their risk-adjusted performance and portfolio enhancement attributes, both in the context of broad alternative property sectors (McIntosh et al , 2017) and sector-specific coverage such as healthcare properties (Newell and Marzuki, 2018a) and student accommodation (Newell and Marzuki, 2018b). Meanwhile, previous studies on data centre properties are confined to issues pertaining to valuation applications (McAllister and Loizou, 2009), planning considerations (Jones, Hillier and Comfort, 2013; Jones, Hillier, Comfort and Clarke-Hill, 2013), sustainability practices (Jones, Hillier and Comfort, 2013; Jones, Hillier, Comfort and Clarke-Hill, 2013; Shuja et al , 2016) and energy consumption and efficiency (Abaunza et al , 2018; Depoorter et al , 2015; Flucker et al , 2018; Oro et al , 2015). To the best of the authors’ knowledge, no previous study has explored the institutional investment opportunity in data centres.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being considered as a nascent asset investment class, the increasing significance of the alternative property sectors has attracted a number of empirical investigations on their risk-adjusted performance and portfolio enhancement attributes, both in the context of broad alternative property sectors (McIntosh et al , 2017) and sector-specific coverage such as healthcare properties (Newell and Marzuki, 2018a) and student accommodation (Newell and Marzuki, 2018b). Meanwhile, previous studies on data centre properties are confined to issues pertaining to valuation applications (McAllister and Loizou, 2009), planning considerations (Jones, Hillier and Comfort, 2013; Jones, Hillier, Comfort and Clarke-Hill, 2013), sustainability practices (Jones, Hillier and Comfort, 2013; Jones, Hillier, Comfort and Clarke-Hill, 2013; Shuja et al , 2016) and energy consumption and efficiency (Abaunza et al , 2018; Depoorter et al , 2015; Flucker et al , 2018; Oro et al , 2015). To the best of the authors’ knowledge, no previous study has explored the institutional investment opportunity in data centres.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2013a, 2013b) classified data centers into: corporate data center; wholesale data center; retail data center; and data-carrier data center. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Jones et al (2013a) identified the characteristics of data centers and studied relevant planning issues in the UK, with the remark that demand already outstripped supply in his time. Concurrently, they also addressed some sustainability issues of UK data centers in another research publication, in particular highlighting the lack of environmental reporting then (Jones et al , 2013b). An American group called 365 Data Centers (2016) compared the cost of new-build data centers versus buying colocation services from third parties, using a time span of 5 years as an indicative framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El término sustentable probablemente se remonte al siglo XIII (Jones, Hillier, Comfort & Clarke-Hill, 2013), aunque su presencia continua, con un sentido económico, ambiental y social se aprecia en foros internacionales, investigaciones y recomendaciones internacionales, desde la década de los sesenta (Bradley, 2007); a la actualidad.…”
Section: La Sustentabilidad De La Información Digitalunclassified
“…Por una parte, la sustentabilidad débil prioriza el desarrollo económico; y, por otra, la sostenibilidad fuerte que subordina las economías al medio ambiente y a la sociedad, reconociendo los límites ecológicos al crecimiento (Jones, Hillier, Comfort & Clarke-Hill, 2013). En algunas naciones como por ejemplo, Reino Unido cada vez más, se exige a las empresas cumplir con normas ambientales mínimas y se reconoce que el negocio sostenible es aquél que trabaja para minimizar el impacto ambiental y social al mismo tiempo que garantiza la estabilidad financiera (Chowdhury Gobinda , 2013).…”
Section: La Sustentabilidad De La Información Digitalunclassified